2022
DOI: 10.7717/peerj.13683
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the anticancer and antioxidant properties of Vicia faba L. pods extracts, a promising source of nutraceuticals

Abstract: Background Pulse crops are considered the major sources of proteins, dietary fiber, micronutrients, and bioactive phytochemicals. Among the numerous pulse crops, broad beans (Vicia faba L.) have received particular attention due to their nutraceutical, functional and economic importance. Our attention was mainly focused on the broad bean pods (VFs), which are the primary by-product of the domestic and industrial processing of broad beans and an attractive source of valuable ingredients. Methods In order to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Recently, Valente et al [ 8 ] investigated the phenolic profile of methanolic extracts from broad bean hulls by the HPLC–DAD–MS/MS method, and the findings highlighted that the predominant phenolic compounds present in this extract were coumaric acid and caffeic acid. Similarly, Ceramella et al [ 15 ] studied the polyphenolic fraction of broad bean hulls extracted with three methods: methanol, 70% aqueous ethanol, and acetone, reporting remarkable amounts of chlorogenic acid, coumaric acid, and ellagic acid. The TPC value found in the analyzed water-based extracts was lower than those reported by Hashemi et al [ 33 ], who obtained methanol-based extracts of broad bean hulls with Soxhlet, percolation, and ultrasound-assisted extraction, which reported TPC values ranging from 54 to 110 mg GAE/g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Valente et al [ 8 ] investigated the phenolic profile of methanolic extracts from broad bean hulls by the HPLC–DAD–MS/MS method, and the findings highlighted that the predominant phenolic compounds present in this extract were coumaric acid and caffeic acid. Similarly, Ceramella et al [ 15 ] studied the polyphenolic fraction of broad bean hulls extracted with three methods: methanol, 70% aqueous ethanol, and acetone, reporting remarkable amounts of chlorogenic acid, coumaric acid, and ellagic acid. The TPC value found in the analyzed water-based extracts was lower than those reported by Hashemi et al [ 33 ], who obtained methanol-based extracts of broad bean hulls with Soxhlet, percolation, and ultrasound-assisted extraction, which reported TPC values ranging from 54 to 110 mg GAE/g.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited literature is currently available about the polyphenolic composition of broad bean hulls. A recent report [ 15 ] identified some important phenolic and flavonoid compounds in broad bean hull extracts using high-performance liquid chromatography (HPLC) with a diode-array detector (DAD). Further scientific studies have reported important pharmacological properties for these active substances, which could justify the exploitation of broad bean hull extracts as a novel source of active molecules [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR spectra of the samples (3 samples for each extraction procedure), placed on the ATR detector, were recorded in triplicate in the range 4000–450 cm −1 , with 32 scans and a resolution of 4 cm −1 . The fingerprint analysis of samples was focused on a specific wavenumber range, the variables selection was carried out by taking out the spectral window 4000–1850 cm −1 [ 16 , 17 ]. The interval 4000–2500 cm −1 contained mainly signals of the stretching vibrations due to -OH functions and aromatic bonds (C-H), and information about phenolic compounds was relatively poor.…”
Section: Methodsmentioning
confidence: 99%
“…The used cell lines (breast cancer cells MCF‐7 and MDA‐MB‐231, melanoma cells A2058 and human mammary epithelial cells MCF‐10A) were obtained from American Type Culture Collection (ATCC) and cultured as already indicated. [ 42 ] The human epithelial neuroblastoma cells SHSY‐5Y and the mouse embryonic fibroblasts BALB/3T3 were also purchased from ATCC and cultured in Dulbecco's modified Eagle's medium high glucose supplemented with 100 U mL −1 penicillin/streptomycin and 10% fetal bovine serum and bovine calf serum, respectively.…”
Section: Methodsmentioning
confidence: 99%